2018
DOI: 10.1136/jech-2018-210592
|View full text |Cite
|
Sign up to set email alerts
|

Natural experiment examining the longitudinal association between change in residential segregation and youth cardiovascular health across race/ethnicity and gender in the USA

Abstract: In light of a continually expanding youth obesity epidemic, the global effort to reduce health inequities may be supported through Parks and Recreation Departments given potential to expand geographic mobility for low resource subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Several approaches were used in the natural experiments as shown in Table 2 . From pre- and post-cohorts with a control group or prospective cohorts ( 36 , 38 , 43 , 52 , 53 , 60 ), controlled before and after studies ( 40 , 46 48 , 57 , 59 , 62 ) before and after studies with and without a control group ( 49 51 , 54 , 55 ), as well as quasi-experimental ( 37 , 56 ), cross-sectional pre- and post-intervention studies with or without a control group ( 35 , 39 , 41 , 42 , 58 , 61 ) providing repeated measures and retrospective studies ( 44 , 45 ). The 24 studies indicated that they were working on PA policies worldwide or nationally, but 25% did not specify the specific PA policy Using natural experiments to evaluate population health interventions: new Medical Research Council guidance ( 36 , 44 , 47 , 51 , 59 , 62 ), 37.5% described the PA policy, but did not evaluate its development ( 35 , 37 , 40 42 , 55 , 57 , 58 , 60 ) and the remaining studies were framed within national public policies on PA or active transportation clearly showing the evaluation of implementation at the level of parks, cities, schools or active transportation ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several approaches were used in the natural experiments as shown in Table 2 . From pre- and post-cohorts with a control group or prospective cohorts ( 36 , 38 , 43 , 52 , 53 , 60 ), controlled before and after studies ( 40 , 46 48 , 57 , 59 , 62 ) before and after studies with and without a control group ( 49 51 , 54 , 55 ), as well as quasi-experimental ( 37 , 56 ), cross-sectional pre- and post-intervention studies with or without a control group ( 35 , 39 , 41 , 42 , 58 , 61 ) providing repeated measures and retrospective studies ( 44 , 45 ). The 24 studies indicated that they were working on PA policies worldwide or nationally, but 25% did not specify the specific PA policy Using natural experiments to evaluate population health interventions: new Medical Research Council guidance ( 36 , 44 , 47 , 51 , 59 , 62 ), 37.5% described the PA policy, but did not evaluate its development ( 35 , 37 , 40 42 , 55 , 57 , 58 , 60 ) and the remaining studies were framed within national public policies on PA or active transportation clearly showing the evaluation of implementation at the level of parks, cities, schools or active transportation ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Objective measurement data of PA was measured with the following instruments including an accelerometer in 7 studies ( 35 , 36 , 40 , 44 , 48 , 58 , 59 ) a pedometer in 1 ( 62 ); and global or geographic location such as GPS, and ACTIVE-PAL-3C in 4 studies ( 36 , 40 , 47 , 50 ). Finally, 8 studies reported other physiologic measures including anthropometrics, vascular resistance, METS, and blood chemistry such as lipid profile, cholesterol, triglycerides, and glycemia ( 38 , 42 44 , 48 , 49 , 55 , 59 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation